Penerapan Metode Design Thinking pada Produk Tas Multifungsi 3 in 1 Universatile - Sahroni, Muhammad; Nugraha, Rizki Agung; Ramadhan, Muhammad Daffa; Kusnanto, Danang (Jurnal EMT KITA, 2026)
UniVersatile is a multifunctional bag innovation developed in 2024 by a group of management students. Born from a campus entrepreneurship project, this product was created to address the needs of urban communities with high mobility who often face the inconvenience of carrying more than one bag in their daily activities. Beyond its functional aspects, UniVersatile also addresses environmental issues stemming from textile waste, as synthetic bags typically have a short lifespan and are difficult to decompose, contributing approximately 15% of domestic waste in Indonesia (KLHK, 2023). Through market research and direct consumer testing, UniVersatile has successfully designed a bag with smart pocket features, special compartments, and durable materials to support efficiency, cleanliness, and sustainability. This innovation not only addresses the practical needs of active users such as students, workers, and travellers, but also provides an environmentally friendly alternative to the fashion product consumption cycle.